Measuring Second Language Pragmatic Competence A Psycholinguistic Perspective - Ellis, Rod (Second Language Acquisition, 2024)
Extending earlier work on grammar, this book investigates the development of tests measuring second language learners' implicit and explicit pragmatic abilities in English. It reports detailed analyses of the use of the tests with two groups of learners and in studies investigating study abroad and the effects of instruction